Aplikasi Limbah Palm Oil Mill Effluent (POME) terhadap Sifat Kimia Tanah pada Perkebunan Kelapa Sawit - Ratnasari, Ika Fitriana Dyah; Devi, Devi; Yanuar Setyawan, Ihda Andrey (Jurnal Media Pertanian, 2024)
Palm oil is a strategic commodity that contributes to the national economy. Indonesia is listed as the largest palm oil producing country and controls more than 50% of the world market. The area of oil palm plantations that continues to increase from year to year has implications for increasing the amount of waste generated from the palm oil sector, one of which is wastewater or known as POME (Palm Oil Mill Effluent). Palm oil wastewater can be used as a substitute for palm fertilizer which contains many nutrients that are needed by oil palm plants. This research was conducted from December 2023 - March 2024 in the community oil palm plantation. The purpose of this study was to determine the effect of POME application on soil chemical properties in community oil palm plantations. This research was conducted in stages: preparation stage, preliminary survey, main survey, soil analysis, observation of FFB productivity and data interpretation. Soil sampling used the Grid Method survey (100 m x 100 m). The number of boring points was 20 points (10 points without wastewater application and 10 points with wastewater application) by observing boring point parameters, namely soil color, adhesiveness and soil texture. The results of soil analysis were compared with the assessment criteria of soil chemical properties and fertility. The results showed that the application of wastewater or POME affected soil chemical properties such as C-Organic, pH, N-total, C/N, P-available, exchangeable bases, CEC, and Base Saturation (KB).